2013
DOI: 10.7150/ijms.5645
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Melatonin on the Proliferation and Differentiation of Chondrocytes from Rat Vertebral Body Growth Plate In Vitro

Abstract: Purpose: Abnormal growth of vertebral body growth plate (VBGP) is considered as one of the etiologic factors in the adolescent idiopathic scoliosis (AIS). It was well-known that melatonin was correlated with the emergence and development of AIS. This study aimed to investigate the effect of melatonin on rat VBGP chondrocytes in vitro.Methods:Chondrocytes were isolated from rat VBGP, and treated with or without melatonin. Cell proliferation was measured by the Alamar Blue assay. Gene expression of collagen type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 45 publications
(44 reference statements)
2
17
0
Order By: Relevance
“…To the best of our knowledge, the current study constitutes the first report on the inhibitory effect of melatonin on the proliferation and differentiation of GPCs in human. In an in vitro study, melatonin at high concentrations (10, 100 µg/mL) showed an inhibitory effect on both the proliferation and differentiation of cultured rat vertebral body growth plate chondrocytes [ 26 ]. After incubation for 24 h in medium containing melatonin, the cell proliferation, gene expression of collagen type II and aggrecan, as well as protein expression of proliferating cell nuclear antigen (PCNA), Sox9 and Smad4 were significantly reduced.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To the best of our knowledge, the current study constitutes the first report on the inhibitory effect of melatonin on the proliferation and differentiation of GPCs in human. In an in vitro study, melatonin at high concentrations (10, 100 µg/mL) showed an inhibitory effect on both the proliferation and differentiation of cultured rat vertebral body growth plate chondrocytes [ 26 ]. After incubation for 24 h in medium containing melatonin, the cell proliferation, gene expression of collagen type II and aggrecan, as well as protein expression of proliferating cell nuclear antigen (PCNA), Sox9 and Smad4 were significantly reduced.…”
Section: Resultsmentioning
confidence: 99%
“…After incubation for 24 h in medium containing melatonin, the cell proliferation, gene expression of collagen type II and aggrecan, as well as protein expression of proliferating cell nuclear antigen (PCNA), Sox9 and Smad4 were significantly reduced. Moreover, it was found that the effects of melatonin could be reversed by the melatonin receptor antagonist luzindole, indicating the involvement of membrane melatonin receptors in these functions [ 26 ]. In a broiler chicken model, Aota et al [ 28 ] noted that pinealectomized chickens had a significantly increased area of labeled hypertrophic zone per total hypertrophic zone compared with control chickens (32.8% ± 12.5% vs. 6.4% ± 5.0%, p < 0.005), as well as an increased number of hypertrophic and proliferative chondrocytes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results are largely consistent with these reports, confirming that melatonin enhances chondrocyte proliferation and the expression of cartilage-associated genes. However, a study using cultured chondrocytes from rat vertebral body growth plates showed that high concentrations of melatonin (4 × 10 −4 M) caused inhibition of cell proliferation and mRNA expression of Col2a1, Aggrecan, Sox9, and Smad4 (Zhong et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The range of the load value and the time of its action are two important determinants of vertebral development. This view reflects our understanding of the complex biological and biomechanical multifactorial processes.…”
Section: Introductionmentioning
confidence: 76%